Transformasi Pembelajaran Pendidikan Agama Islam di Era Digital: Sebuah Kajian Pustaka - Naimi, Nadlrah; Nursakinah, Nursakinah; Sitepu, Melyani Sari; Sitepu, Juli Maini (Faculty of Teacher Training and Education of Undaris, 2025)
The development of information and communication technology in the era of Industrial Revolution4.0 and Society 5.0 has brought major changes in the world of education, including in the field of IslamicReligious Education (PAI). This article aims to examine the transformation of the PAI learning model in thedigital era through a literature review approach to accredited scientific literature in the last five years. Theresults of the study show that PAI learning has shifted from a teacher-centered lecture-based model tostudent-centered learning that integrates digital technology such as the Learning Management System(LMS), educational videos, Islamic moral gamification, and virtual reality in worship simulations. Althoughdigitalization provides many opportunities to increase the effectiveness and engagement of learning,challenges such as low digital literacy, gaps in access to technology, and distortion of religious informationare also emerging. Therefore, a strategy is needed to strengthen the digital capacity of educators, developlearning materials based on religious moderation, and equalize access to technology to ensure that thetransformation of PAI learning in the digital era remains relevant, inclusive, and rooted in Islamic valuesrahmatan lil 'alamin.Keywords: Islamic Religious Education, Learning Transformation, Digital Era, Digital Literacy